Manajemen Dakwah dan Moderasi Beragama di Kawasan Wisata Mandalika Lombok Tengah - wadi, Hamzanwadi Hamzan (UIN Mataram, 2023)
This research basically seeks to explore the management of da'wah and religious moderation in the Mandalika Tourism Area of ??Central Lombok. Apart from that, this research also seeks to provide an overview of the activities of da'wah and religious moderation for local communities and tourists who come to visit to enjoy the beauty of various forms. tourism in Mandalika. The results of research using qualitative descriptive research methodology along with approaches and strategies show that; da'wah management and religious moderation in the Mandalika area of ??Central Lombok. Da'wah management is carried out through programs at the Nurul Bilad Mosque, which is the center for da'wah, including the hiziban program, spiritual recitation or prayer, social service, and greeting tourists who visit the Mandalika area, especially at the Nurul Bilad Mosque. The religious moderation that is carried out is socializing the community, being a mediator in resolving conflicts, undergoing an interfaith youth camp program, developing converts, and not placing restrictions on any tourists.